The Role of Technology in Enhancing Library Services in Developing Countries: Comparative Studies on West African Libraries - Dada, Kayode Sunday John (Information Research Communications, 2026)
Libraries across West Africa are navigating a difficult transition shaped by decades of underinvestment, persistent infrastructure gaps, and rapidly growing community information needs that have outpaced institutional capacity. Although technology theoretically offers a pathway to overcome these constraints, its adoption in West African library settings remains uneven, with outcomes varying significantly across national and institutional contexts. This study examines how technology-driven interventions are reshaping library services in four West African countries-Nigeria, Ghana, Senegal, and Côte d'Ivoire-and identifies the structural and contextual factors that determine whether such interventions succeed or stall. A mixed-methods comparative design was employed, involving structured questionnaires administered to 312 library professionals across 24 academic, public, and special libraries in the four countries, supplemented by semi-structured interviews with 36 purposively selected library directors and technology officers. Quantitative data were analysed using descriptive statistics and one-way ANOVA, while qualitative responses underwent thematic analysis grounded in the Technology Acceptance Model and the Diffusion of Innovations framework. Results showed that Integrated Library Systems (ILS) and digital catalogue access recorded the highest adoption rates across all four countries (68-84%), whereas institutional repositories and AI-assisted reference tools were limited to a small number of well-resourced institutions. Technology integration significantly improved catalogue access times by a mean of 47%, enhanced user satisfaction scores, and expanded the reach of extension services. However, pronounced country-level differences emerged, with Nigerian and Ghanaian libraries demonstrating stronger institutional adoption than their Senegalese and Ivorian counterparts. These differences closely tracked variations in electricity reliability, internet penetration, and budget allocation. The findings indicate that technology alone does not transform library services; sustained electricity, affordable connectivity, trained staff, and institutional leadership that treats technology as a long-term programmatic commitment rather than a short-term project expenditure are the critical determinants of successful outcomes.
Keywords: Comparative Library Studies; Developing Countries; Digital Library Services; Library Technology; Technology Acceptance; West Africa.